A corpus-assisted critical discourse analysis of COVID-19 vaccination-related news discourse in the Malaysian mainstream media - Nadhratunnaim Abas; Roslina Abdul Aziz; Syamimi Turiman; Nor Shidrah Mat Daud (Penerbit Universiti Kebangsaan Malaysia, 2023)
The deadly impact of COVID-19 has caused authorities worldwide to resort to vaccination as an exit strategy. Some have even imposed vaccination as a mandatory policy to ensure social compliance. Many studies have focused on the issues of discrimination and polarisation due to the virus and the vaccines, but very little is known about vaccination as a process of generating compliance, especially in the Malaysian context. Hence, the paper aims to address this gap by examining how COVID-19 vaccination is discursively profiled in the Malaysian mainstream media. The study utilised corpus analysis and Discourse-Historical Approach (DHA) of Critical Discourse Analysis (CDA) in examining the corpus of 1514 vaccination-related news reports in the Malaysian mainstream media amounting to approximately 924028 tokens. Through the discursive strategies of referential/nomination and predication, the findings indicated that vaccination was strongly affiliated with those representing the government and its ideology. To generate compliance, vaccination was described as synonymous with the national agenda. Hence, vaccination was dominantly assigned positive labels that promoted this ideology, except for the very few negative labels attributed to the mandatory policy, the effects of vaccination and the deadly impact of COVID-19 infection. The study not only contributes to the vast literature on COVID-19 but it also provides a linguistic analysis that combines corpus techniques and CDA to examine a discursive practice that can further pave the way for uncovering the ideological discourse in the mainstream media.